2020
DOI: 10.1021/acscatal.0c03897
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate-Induced Structural Evolution of Pd Catalyst for Selective Hydrogenation of Acetylene

Abstract: This work describes the transformation of Pd species under reaction condition to control the reactivity of heterogeneous catalysts, in which the real active sites for hydrogenation differ from simple Pd sites on a carbon nanofiber. Specifically, in the presence of C2H2/C2H4/H2 reaction mixtures, a permeable amorphous hydrocarbon overlayer is formed with simultaneous insertion of carbon atoms into Pd lattice that drives the formation of low coordinated Pd-carbide, thus providing more reactive Pd-Csub@Clayer sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 51 publications
4
55
0
Order By: Relevance
“…Furthermore, the intrinsic activities, namely, turnover frequency (TOF with the unit of s –1 ), are calculated based on the following formula at a low level of C 2 H 2 conversion (<15%), where A acetylene means the converted acetylene mole per minute (mol/min), n stands for the Cu mole (mol), while D refers to metal dispersion (%) determined by N 2 O titration analysis From Cu/Fe 1 MgO x to Cu/Fe 0.12 MgO x , TOF increases and then reduces when the highest value of 0.048 s –1 is achieved in the Cu/Fe 0.16 MgO x sample (Figure A), indicating that the optimal turnover frequency is decided by an appropriate interface structure adjusted by the Cu-Fe y MgO x interfacial interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the intrinsic activities, namely, turnover frequency (TOF with the unit of s –1 ), are calculated based on the following formula at a low level of C 2 H 2 conversion (<15%), where A acetylene means the converted acetylene mole per minute (mol/min), n stands for the Cu mole (mol), while D refers to metal dispersion (%) determined by N 2 O titration analysis From Cu/Fe 1 MgO x to Cu/Fe 0.12 MgO x , TOF increases and then reduces when the highest value of 0.048 s –1 is achieved in the Cu/Fe 0.16 MgO x sample (Figure A), indicating that the optimal turnover frequency is decided by an appropriate interface structure adjusted by the Cu-Fe y MgO x interfacial interaction.…”
Section: Resultsmentioning
confidence: 99%
“…As determined by STEM and thermogravimetric analysis-mass spectrometry (TG-MS) analysis (Figures S7 and S8), the morphology and structure of the Cu/Fe 0.16 MgO x catalyst are well-preserved and the generation of oligomers is also effectively inhibited during 40 h on stream. Furthermore, the intrinsic activities, namely, turnover frequency (TOF with the unit of s −1 ), are calculated based on the following formula at a low level of C 2 H 2 conversion (<15%), 42 where A acetylene means the converted acetylene mole per minute (mol/min), n stands for the Cu mole (mol), while D refers to metal dispersion (%) determined by N 2 O titration analysis. 43 = ×…”
Section: å Exists (Exafs Analysis In Figuresmentioning
confidence: 99%
“…T‐Pd1/UIO‐66‐NH 2 demonstrates 40.5 kJ mol −1 of E a (with a turnover frequency of 0.132 s −1 ), close to that of Pd NPs/UIO‐66‐NH 2 (see Figure 10F), indicating that in situ treating can effectively reduce the activation barrier and enhance catalytic activity. [ 95 ] Moreover, T‐Pd 1 /UIO‐66‐NH 2 also shows excellent catalytic stability within 1600 min of the reaction (see Figure 10G). The results of X‐ray absorption spectroscopy (XAS) and DFT calculation demonstrated that the in situ adsorbate (H 2 )‐induced lattice compression of MOFs can upshift the N2 p band and decrease the d ‐orbital overlap of Pd (with antibonding orbital filling), which thermodynamically facilitates the activation and dissociation of H 2 and the desorption of C 2 H 4 (see the insets in Figure 10G).…”
Section: Heterogeneous Catalysis Applications Of Afcsmentioning
confidence: 99%
“…Incorporation of C atoms leads to the expansion of the Pd lattice, which is proportional to the C/Pd concentration ratio. Under the reaction conditions of hydrogenation, the C/Pd concentration ratio reaches a maximum of 0.13:1. , Recently, Jin et al have synthesized PdC x nanocrystals with a tunable C/Pd concentration ratio (from 0.04 to 0.18:1) by adjusting the reaction time at 200 °C . Moreover, 0.18:1 is regarded as the saturation C/Pd concentration ratio, which cannot be improved further by both increasing the reaction temperature to 250 °C and prolonging the reaction time.…”
Section: Introductionmentioning
confidence: 99%